2010
DOI: 10.1002/adfm.201001956
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Buffering Technique for Aqueous Processing of Zinc Oxide Nanostructures and Interfaces, and Corresponding Improvement of Electrodeposited ZnO‐Cu2O Photovoltaics

Abstract: A novel buffering method is presented to improve the stability of zinc oxide processed in aqueous solutions. By buffering the aqueous solution with a suitable quantity of sacrificial zinc species, the dissolution of functional zinc oxide structures and the formation of unwanted impurities can be prevented. The method is demonstrated for ZnO films and nanowires processed in aqueous solutions used for the selective etching of mesoporous anodic alumina templates and the electrochemical deposition of Cu2O. In both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 41 publications
(59 reference statements)
4
117
0
Order By: Relevance
“…Their reported efficiencies, however, are still less than that of planar equivalents [129] such that optimization of the nanostructure geometry and materials properties is required. In recent work, it was demonstrated that care must be taken when processing ZnO nanostructures in aqueous solutions, and a novel buffering method was developed to improve the properties of the electrochemically synthesized Cu 2 O-ZnO interface [130].…”
Section: Performance Of Ultra-low-cost Nanostructured Inorganic Solarmentioning
confidence: 99%
“…Their reported efficiencies, however, are still less than that of planar equivalents [129] such that optimization of the nanostructure geometry and materials properties is required. In recent work, it was demonstrated that care must be taken when processing ZnO nanostructures in aqueous solutions, and a novel buffering method was developed to improve the properties of the electrochemically synthesized Cu 2 O-ZnO interface [130].…”
Section: Performance Of Ultra-low-cost Nanostructured Inorganic Solarmentioning
confidence: 99%
“…6(a). The arcs are compressed because of the inhomogeneity of the electrical properties of the measured interface [15,35]. The shape and size of the compressed semicircle are related to the photoinjected electron transport in the Cu NWs/Cu 2 O film or the back reaction at the Cu NWs/Cu 2 O-electrolyte interface, and the smaller semicircle represents the lower charge-transport resistance.…”
Section: Resultsmentioning
confidence: 99%
“…At this point, the current reaches a local minimum (4). At the end of the anodization process, the current rapidly increases, accompanied by vigorous gas bubbles (5).…”
Section: Aao Template-figuresmentioning
confidence: 99%
“…Nanowire arrays have attracted much attention in photovoltaic devices, [1][2][3][4] sensing, 5,6 plasmonics, 7 surface enhanced Raman scattering, 8 high density data storage, 9 photocatalysts, 10 and nanobiotechnology, 11 due to their unique electrical, optical, magnetic, and chemical properties which are different from those in the bulk state. In photovoltaics nanowire arrays are of particular interest for costeffective organic and hybrid solar cells, whose near-optimal architecture is proposed to consist of arrays of nanostructures (approximately 200 nm long).…”
mentioning
confidence: 99%